Private sector quality of care for maternal, new-born, and child health in low-and-middle-income countries: a secondary review - Morris, Georgina; Maliqi, Blerta; Lattof, Samantha R.; Strong, Joe; Yaqub, Nuhu (Frontiers in Global Women's Health, 2024)
The private sector has emerged as a crucial source of maternal, newborn, and child health (MNCH) care in many low- and middle-income countries (LMICs). Quality within the MNCH private sector varies and has not been established systematically. This study systematically reviews findings on private-sector delivery of quality MNCH care in LMICs through the six domains of quality care (QoC) (i.e., efficiency, equity, effectiveness, people-centered care, safety, and timeliness). We registered the systematic review with PROSPERO international prospective register of systematic reviews (registration number CRD42019143383) and followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) Statement for clear and transparent reporting of systematic reviews and meta-analyses. Searches were conducted in eight electronic databases and two websites. For inclusion, studies in LMICs must have examined at least one of the following outcomes using qualitative, quantitative, and/or mixed-methods: maternal morbidity, maternal mortality, newborn morbidity, newborn mortality, child morbidity, child mortality, service utilization, quality of care, and/or experience of care including respectful care. Outcome data was extracted for descriptive statistics and thematic analysis. Of the 139 included studies, 110 studies reported data on QoC. Most studies reporting on QoC occurred in India (19.3%), Uganda (12.3%), and Bangladesh (8.8%). Effectiveness was the most widely measured quality domain with 55 data points, followed by people-centered care (n = 52), safety (n = 47), timeliness (n = 31), equity (n = 24), and efficiency (n = 4). The review showed inconsistencies in care quality across private and public facilities, with quality varying across the six domains. Factors such as training, guidelines, and technical competence influenced the quality. There were also variations in how domains like “people-centered care” have been understood and measured over time. The review underscores the need for clearer definitions of “quality” and practical QoC measures, central to the success of Sustainable Development Goals (SDGs) and equitable health outcomes. This research addresses how quality MNCH care has been defined and operationalized to understand how quality is delivered across the private health sector and the larger health system. Numerous variables and metrics under each QoC domain highlight the difficulty in systematizing QoC. These findings have practical significance to both researchers and policymakers. Systematic Review Registration https://bmjopen.bmj.com/content/10/2/e033141.long, Identifier [CRD42019143383].